Board Meeting Attendance and Corporate Tax Avoidance: Evidence from the UK. Issue 1 (January 2020) - Barros, Victor; Sarmento, Joaquim Miranda
Abstract: Is corporate tax avoidance associated with board meetings and attendance? Despite the large amount of research in management and finance on the impact of boards in several firm decisions, there is very little research that associates boards with tax avoidance. In this article, we look at firms listed on the London Stock Exchange during the period 2002–2015 and analyze whether a higher frequency of board meetings in the UK is associated with lower corporate tax liability. Our findings show that board meetings and attendance rate exert opposite effects, although the frequency of meetings is associated with lowering the tax liability. However, the association does not hold in a linear way. Tax-avoiding firms pay about 3 percent less effective tax rate, which is associated with average levels of meetings frequency, whereas those in the upper tail of the effective tax rate distribution benefit from a combined decrease of about 5–6 percent in the effective tax rate. The results conclusively support the view that a more resilient and focused control of board members mitigates opportunistic behavior and rent-seeking, thus enabling managers to engage in tax avoidance strategies.